2015
DOI: 10.1002/jor.22843
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of the effectiveness of carpal tunnel release on median nerve deformation

Abstract: To assess the biomechanical effect of carpal tunnel release (CTR), we evaluated the deformation and displacement patterns of the median nerve before and after CTR in carpal tunnel syndrome (CTS) patients. Sixteen wrists of 14 idiopathic CTS patients who had open CTR and 26 wrists of 13 asymptomatic volunteers were evaluated by ultrasound. Cross-sectional images of the carpal tunnel during motion from full finger extension to flexion were recorded. The area, perimeter, aspect ratio of a minimum enclosing rectan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Previous studies have already tried to shed light on MN [16] or carpal tunnel stiffness [15], as well as MN deformation after carpal tunnel release [18]. Similarities between our approach and elastographic methods exist: in particular, strain elastography is based on external compression and provides information on tissue deformation to derive a non-quantifiable elasticity grade [26, 27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have already tried to shed light on MN [16] or carpal tunnel stiffness [15], as well as MN deformation after carpal tunnel release [18]. Similarities between our approach and elastographic methods exist: in particular, strain elastography is based on external compression and provides information on tissue deformation to derive a non-quantifiable elasticity grade [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the prognostic value of US findings is still at debate and little literature on the prognostic value of US is available. Only recently have attempts been made to further quantify intraneural changes of the MN, such as by sonoelastography [15, 16] and MN deformation assessment [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Various studies have used intraoperative ultrasonography for assistance in open and percutaneous carpal tunnel release. 1,2,[14][15][16][17][18] They have reported that ultrasound is useful in visualizing the potential risks of injury to the flexor tendon and neurovascular bundles, in evaluating the completeness of the release and in identifying causes of failure such as incomplete release, and in observing the recovery process of the median nerve after the release. However, we have not found an article describing the actual techniques for use of ultrasound along with an endoscopic procedure to minimize complications and confirm complete release.…”
Section: Discussionmentioning
confidence: 99%
“…The confirmatory value of US after CTR is unknown. Some studies have described that postoperative US follow-up might allow prediction of the surgical outcome by measuring the postoperative CSA of the median nerve [14]. Most authors describe a decrease in the median nerve CSA following CTR, admittedly with great variation [6, 10, 15 -18].…”
Section: Discussionmentioning
confidence: 99%